Analysis of Gen Z’s Continuous Intention to Use Tiktok Shop in DKI Jakarta Through the UTAUT2 Perspective - Sam Pradita, Ferdyn Nurwenda; Adityaputra, Muhammad Rizki; Gunadi, Willy (Journal Research of Social Science, Economics, and Management, 2025)
Along with technological development, platforms that combine e-commerce and social media—known as social commerce—have emerged. In Indonesia, TikTok Shop has grown rapidly, as reflected by the increase in Gross Merchandise Value (GMV). TikTok Shop enables users to shop online while engaging with social media in a single application without switching platforms. This study aims to analyze the phenomenon of the growing use of TikTok Shop by examining the role of attributes from the Unified Theory of Acceptance and Use of Technology 2 (UTAUT2), such as performance expectancy, effort expectancy, social influence, facilitating conditions, hedonic motivation, habit, and gender, as well as additional variables including perceived price-saving orientation, risk, and trust. Data were collected through an online questionnaire involving 200 Generation Z respondents aged 17 to 29 years, residing in DKI Jakarta, who had made purchases through TikTok Shop within the past three months. Using a quantitative approach with the analysis of the Partial Least Squares Structural Equation Model (PLS-SEM), the results showed that habit, price-saving orientation, and trust exerted a positive and significant influence on the intention to use TikTok Shop. Conversely, performance expectancy, effort expectancy, social influence, facilitating conditions, hedonic motivation, and perceived risk did not demonstrate significant influence. Furthermore, gender did not moderate the relationships among these variables. These findings confirm that habit, cost-saving orientation, and trust play dominant roles in fostering the continuous intention of TikTok Shop use among Generation Z, offering valuable insights for service providers to develop more effective strategies.